STUDI PERTUMBUHAN MULTIANTAGONIS TRICHODERMA SP. DAN STREPTOMYCES SP. DALAM SUSPENSI AKAR, HUMAT CAIR DAN EKSTRAK KENTANG GULA - Ika Nur Fitriana; Penta Suryaminarsih; Wanti Mindari; Sri Wiyatiningsih (UPN VETERAN JAWA TIMUR, 2019)
Multiplication of multiantagonist Trichoderma sp. and Streptomyces sp. done on agar plates and liquid media covered for multiplication and facilitate cell harvesting. Root suspension containing microorganisms and humic liquid is a biopesticide and fertilizer material that was expected to be more effective for biodegradation of biological agents to have more value. This study aims to determine the ability of life and propagation Trichoderma sp. and Streptomyces sp. in root suspension, humic liquid and sugar potato extract. This study used a descriptive observations on days 10th, 14th and 17th before inoculation of Trichoderma sp. and Streptomyces sp showed that in liquid humic medium there are microorganisms but fewer number of microorganisms on root suspension media. The 17th day after inoculation of the Trichoderma sp. and Streptomyces sp showed that in the humic liquid medium, the biological agent did not grow, while the root suspension medium was only Streptomyces growing but not as much as developed on sugar potato extract.